The Autobiography of Fidel Castro - Fuentes, Norberto (New York W. W. Norton & Company, 2010)
Prizewinning author and journalist Norberto Fuentes was once a revolutionary: a writer with privileged access to Fidel Castro's inner circle during some the most challenging years of the revolution. But in the late 1990s, as the regime began sending its oldest comrades to the firing squad, he became A Man Who Knew Too Much. Escaping a death sentence and now living in exile, Fuentes has written a brilliant, satirical, and utterly captivating "autobiography" of the Cuban leaderin Fidel's own arrogant and seductive languagediscussing everything from Castro's early sexual experiences in Birán to his true feelings about Che Guevara and his philosophy on murder, legacy, and state secrets. From publisher description
Include Maps and Illustrations
Keywords: Cuba -- Heads of State